Scientific value of systematic reviews: survey of editors of core clinical journals - Meerpohl, Jörg J.; Herrle, Florian (PLOS ONE, 2012)
Background Synthesizing research evidence using systematic and rigorous methods has become a key feature of evidence-based medicine and knowledge translation. Systematic reviews (SRs) may or may not include a meta-analysis depending on the suitability of available data. They are often being criticised as ‘secondary research’ and denied the status of original research. Scientific journals play an important role in the publication process. How they appraise a given type of research influences the status of that research in the scientific community. We investigated the attitudes of editors of core clinical journals towards SRs and their value for publication. Methods We identified the 118 journals labelled as “core clinical journals” by the National Library of Medicine, USA in April 2009. The journals’ editors were surveyed by email in 2009 and asked whether they considered SRs as original research projects; whether they published SRs; and for which section of the journal they would consider a SR manuscript. Results The editors of 65 journals (55%) responded. Most respondents considered SRs to be original research (71%) and almost all journals (93%) published SRs. Several editors regarded the use of Cochrane methodology or a meta-analysis as quality criteria; for some respondents these criteria were premises for the consideration of SRs as original research. Journals placed SRs in various sections such as “Review” or “Feature article”. Characterization of non-responding journals showed that about two thirds do publish systematic reviews. Discussion Currently, the editors of most core clinical journals consider SRs original research. Our findings are limited by a non-responder rate of 45%. Individual comments suggest that this is a grey area and attitudes differ widely. A debate about the definition of ‘original research’ in the context of SRs is warranted.